Barriers to successful climate change policy implementation in Tanzania - Ampaire, Edidah L.; Okolo, Wendy; Acosta, Mariola; Jassogne, Laurence T.P.; Twyman, Jennifer; Muindi, Pauline; Mwongera, Caroline (2016)
The agricultural sector is central to Tanzania’s economy, natural resources and livelihoods. Climate change and climate variability presents adverse effects to the growth of the agriculture sector and the livelihoods of 80 percent of Tanzanians (MAFC, 2014). Owing to this, the Tanzania government has ratified several climate-resilient strategies, policies and plans geared towards climate adaptation and mitigation. This Info Note assesses how and to what extent climate change concerns have been mainstreamed in the existing and most recent national strategies, policies, plans and legal legislations of Tanzania. Furthermore, the Info Note focuses on the climate change formulation levels from national to local, and implications on policy implementation in Tanzania.